ACCOUNTING STUDENTS NEEDS IN LEARNING ENGLISH FOCUSING ON THE PLANTATION COMPANY SECTOR AT POLYTECHNIC LPP YOGYAKARTA - Endang Lestari (Jurnal Scientia, 2023)
In recent years, the Indonesian government has been emphasizing the importance of vocational education to address skills gaps, promote economic growth, and reduce youth unemployment. Vocational education in Indonesia plays a crucial role in equipping students with practical skills, fostering industry partnerships, and contributing to the development of a skilled and competent workforce that supports the country's economic and social advancement. It is in line with English as one of the skills that must be learned by the students to face the work field. The appropriate learning materials should be based on the needs. This study is a quantitative descriptive that aims to find out the Accounting student’s need that focuses on plantation company in learning English at Polytechnic LPP Yogyakarta. There were 49 respondents classified as Diploma 3 level. The researcher used a questionnaire to collect the data. The quantitative data were analyzed using descriptive statistics. The data with the highest percentage are presented in the table. Based on the need analysis, the student found descriptive and report text in their life. The topics include Cost and Budgeting, Stock, Auditing, taxation, and Financial Statements. Grammar and vocabulary become obstacles in learning English. In speaking activities, they want to have a pair conversation. The main goal of learning English is to be fluent in communicating using English. They prefer to have a group discussion. The role of the lecturer should be interactive and motivate the learner and apply current technology and fun learning methods. Written literature is their favorite learning source. The results of this study can be used for developing English material.